Pemetaan Saluran Irigasi sebagai Upaya Penyediaan Air bagi Kebutuhan Pertanian (Studi Kasus: Desa Sindangsari, Kecamatan Ciranjang, Kabupaten Cianjur) - Fifi Fata'tiatul Hidayah; Lailatul Qodriyah Agne Verawati; Hermanu Widjaja (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Irrigation Network Rehabilitation activities are the main supporting activities in the agricultural business by providing irrigation water for the realization of food sovereignty, particularly rice. Lowland rice is the principal agricultural commodity in Sindangsari village, Cianjur. More than 50 per cent of this village's rice fields are irrigated. Unfortunately the current irrigation conditions are classified as dry due to drought, thus inhibiting rice production. In addition to being dry, there are also many points of garbage accumulation that pollute the water flow and even obstruct the water flow. This activity aims at mapping the condition of irrigation canals in Sindangsari village. The irrigation channel map has been successfully prepared and approved by the Cianjur Regency Regional Planning Agency and the Ciranjang District Water Resources Management Office, so that more policies on irrigation issues in the area can be taken into consideration. Key words: irrigation, network rehabilitation, rice, rice field